2014
DOI: 10.7860/jcdr/2014/8404.4592
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Management of a Haemophilic Patient- A Clinical Perspective

Abstract: A 16-year-old boy reported at ESIC Dental College and Hospital, Rohini, Delhi with the chief complaint of pain and swelling in lower left back teeth region since 3-4 days. Medical history revealed that the patient was suffering from Haemophilia A. The patient also gave H/o paralysis of left side of body in the year 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…From Dudeja et al (2014) – ‘The patient first reported with gum bleed at the age of 1 year and 6 months and was diagnosed with haemophilia at the age of three years. There was associated family history of haemophilia (maternal cousin suffered from it)’.…”
Section: The Price 2020 Explanation and Elaboration Documentmentioning
confidence: 99%
“…From Dudeja et al (2014) – ‘The patient first reported with gum bleed at the age of 1 year and 6 months and was diagnosed with haemophilia at the age of three years. There was associated family history of haemophilia (maternal cousin suffered from it)’.…”
Section: The Price 2020 Explanation and Elaboration Documentmentioning
confidence: 99%
“…When a patient with a hereditary bleeding disorder develops pain associated with irreversible pulpitis or necrosis, endodontic treatment is a good alternative to extraction and is considered relatively safe in terms of the potential risk of bleeding [ 58 ]. Any bleeding that occurs as a result of the presence of living pulp in the canal can be limited by rinsing the root canals with sodium hypochlorite solution [ 58 ]. An alternative is a calcium hydroxide dressing, which has drying properties [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Any bleeding that occurs as a result of the presence of living pulp in the canal can be limited by rinsing the root canals with sodium hypochlorite solution [ 58 ]. An alternative is a calcium hydroxide dressing, which has drying properties [ 58 , 59 ]. When developing root canals, it is extremely important to observe the working length and use apex locators [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations